SYNTHESIS AND INFRARED STUDY OF SOME NEW SnC2O4Cl2 ADDUCTS AND COMPLEXES - HASSAN ALLOUCH; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Eight new SnC2O4Cl2 adducts and derivatives have been synthesized and studied by infrared. Ionic discrete structures have been suggested on the basis of infrared data, the environment around the tin (IV) centre being tetrahedral or octahedral.